2023
DOI: 10.1111/risa.14111
|View full text |Cite
|
Sign up to set email alerts
|

Narrative persuasion and psychological distance: Analyzing the effectiveness of distance‐framed narratives in communicating ocean plastic pollution

Abstract: Narratives have been identified as an effective tool to communicate seemingly abstract and uncertain risks. This study integrates the construal level theory of psychological distance and narrative persuasion to examine how distance‐framed narratives influence young adults’ attitude, behavioral intention, and policy support related to ocean plastic pollution. Results from an experimental survey (N = 889) indicate that the narrative featuring socially close characters and spatially close location is least effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Such heightened transportation may serve to reduce hypothetical, spatial, and temporal psychological distances, as they are situated within the unfolding events, feeling that the depicted consequences are occurring in close proximity and in the present moment. Empirically, Liu and Yang have examined the association between transportation and psychological distance in both environmental and health contexts, and found that transportation experience can make the recipients perceive the health and environmental threats as temporally closer (Liu & Yang, 2020, 2023).…”
Section: Strategic Use Of Narrative and Psychological Distancementioning
confidence: 99%
“…Such heightened transportation may serve to reduce hypothetical, spatial, and temporal psychological distances, as they are situated within the unfolding events, feeling that the depicted consequences are occurring in close proximity and in the present moment. Empirically, Liu and Yang have examined the association between transportation and psychological distance in both environmental and health contexts, and found that transportation experience can make the recipients perceive the health and environmental threats as temporally closer (Liu & Yang, 2020, 2023).…”
Section: Strategic Use Of Narrative and Psychological Distancementioning
confidence: 99%
“…However, a consistent trend is not evident when employing narratives as a medium to convey distance cues. In a study on plastic pollution (Liu and Yang, 2023), researchers embedded social and spatial distance cues in the storylines, tailoring the narratives to resonate uniquely with the audience. Unlike the findings from distance-framed non-narrative studies, audiences responded more favorably to narratives with mismatched distance cues (e.g.…”
Section: Psychological Distancementioning
confidence: 99%
“…Narratives are highly effective tools in fostering social and behavioral change (Braddock & Dillard, 2016). Recent research also suggests that narratives may achieve even higher persuasiveness when customized according to the audience traits (Gray & Harrington, 2011;Liu & Yang, 2023). However, as customizing even the simplest narrative may require much human labor, ChatGPT is well-equipped to create customized narratives for various purposes at a very low cost.…”
Section: Chatgpt As a Narrative Storytellermentioning
confidence: 99%